β-Arrestin 2 mediates arginine vasopressin-induced IL-6 induction via the ERK1/2-NF-κB signal pathway in murine hearts - Sun Shu-zhen; Cao Hong; Yao Na; Zhao Ling-ling; Zhu Xiao-fang; Ni Er-an; Zhu Qi; Zhu Wei-zhong (Acta Pharmacologica Sinica, 2020)
Evidence to date suggests that β-arrestins act beyond their role as adapter proteins. Arginine vasopressin (AVP) may be a factor in inflammation and fibrosis in the pathogenesis of heart failure. In the present study we investigated the effect of AVP on inflammatory cytokine IL-6 production in murine hearts and the impact of β-arrestin 2-dependent signaling on AVP-induced IL-6 production. We found that administration of AVP (0.5 U/kg, iv) markedly increased the levels of IL-6 mRNA in rat hearts with the maximum level occurred at 6 h. In β-arrestin 2 KO mouse hearts, deletion of β-arrestin 2 decreased AVP-induced IL-6 mRNA expression. We then performed in vitro experiments in adult rat cardiac fibroblasts (ARCFs). We found that AVP (10−9–10−6 M) dose-dependently increased the expression of IL-6 mRNA and protein, activation of NF-κB signaling and ERK1/2 phosphorylation, whereas knockdown of β-arrestin 2 blocked AVP-induced IL-6 increase, NF-κB activation and ERK1/2 phosphorylation. Pharmacological blockade of ERK1/2 using PD98059 diminished AVP-induced NF-κB activation and IL-6 production. The selective V1A receptor antagonist SR49059 effectively blocked AVP-induced NF-κB phosphorylation and activation as well as IL-6 expression in ARCFs. In AVP-treated mice, pre-injection of SR49059 (2 mg/kg, iv) abolished AVP-induced NF-κB activation and IL-6 production in hearts. The above results suggest that AVP induces IL-6 induction in murine hearts via the V1A receptor-mediated β-arrestin2/ERK1/2/NF-κB pathway, thus reveal a novel mechanism of myocardial inflammation in heart failure involving the V1A/β-arrestin 2/ERK1/2/NF-κB signaling pathway.